INTESTINAL HISTOLOGY OF THE GROUPER Epinephelus lanceolatus × fuscoguttatus ADMINISTERED WITH SIMPLICIA PAPAYA - Rita Rostika; Ayu Yustiati; Achmad Rizal; Mochammad Rudyansyah; Lantun Paradhita Dewanti (BIOTROPIA, 2019)
The grouper (Epinephelus sp.) is a marine fish species that is widely cultivated commercially for hatchery and grow–out purposes and shows a promising production prospect. The structure and development of fish intestines are influenced by internal and external factors, such as water quality, feed quality, and feed quantity. However, even though the protein content in the diet is relatively high, the growth performance of Epinephelus lanceolatus × Epinephelus fuscoguttatus remains low. This study aimed to determine the effect of papaya simplicia supplementation on grouper growth, specifically absolute weight gain and protein efficiency ratio. The experiment used a Completely Randomized Design with five treatments and three replications (A: papaya simplicia 5%, B: 3.75%, C: 2.5%, D: 1.25%, and E: 0% as the control). Groupers were reared in floating net cages in Pangandaran Regency, Indonesia. Supplementation of papaya simplicia at 3.75% and 5% increased the number of necrotic cells (169 and 183 cells, respectively), as well as the number of goblet cells. The addition of papaya simplicia at 5%, 3.75%, and 2.5% increased the absolute weight gain to 161.36 g, 152.19 g, and 152.09 g, respectively. Supplementation at 5% and 3.75% also increased the protein efficiency ratio to 3.18% and 3.19%, respectively.